Marketing Management: Education Business Strategi Marketing Universitas Swasta Studi Kasus Universitas Kristen Satya Wacana - Anggreani Sarah Yonaha Saroinsong (Jurnal Syntax Admiration, 2024)
This research aims to provide theoretical benefits by developing science and theory regarding SWOT analysis and the promotion mix of Satya Wacana Christian University (UKSW), as well as adding literature for further research. The type of research that will be used by the researcher is a qualitative approach and qualitative research. The researcher uses a qualitative approach with a type of descriptive research. The unit of analysis in this study is SWOT "Satya Wacana Christian University", which is a reference for carrying out promotional activities. In this study, there are 2 research observation units, the Public Relations and Alumni Promotion Bureau as actors and persons in charge of UKSW's "promotion and media used" activities in carrying out promotional activities. The researcher obtained the results that the promotional activities carried out by UKSW were appropriate.